Co-assessment of cell cycle and micronucleus frequencies demonstrates the influence of serum on the in vitro genotoxic response to amorphous monodisperse silica nanoparticles of varying sizes. Issue 8 (December 2014) - Gonzalez, Laetitia; Lukamowicz-Rajska, Magdalena; Thomassen, Leen C. J.; Kirschhock, Christine E. A.; Leyns, Luc; Lison, Dominique; Martens, Johan A.; Elhajouji, Azeddine; Kirsch-Volders, Micheline
Abstract Serum proteins have been shown to modulate the cytotoxic and genotoxic responses to nanomaterials. The aim was to investigate the influence of serum on the induction of micronuclei (MN) by nanoparticles (NPs) of different sizes. Therefore, A549 human lung carcinoma cells and amorphous monodisperse silica nanoparticles (SNPs) were used as models. Assessment of the cell viability, cell cycle changes and induction of MN by SNPs ranging from 12 to 174 nm was performed in presence or absence of serum, applying the in vitro flow cytometry-based MN assay. Here, it has been demonstrated that serum has an influence on these end points, with a lower cell viability in absence of serum compared with the presence of serum. Further, cell cycle changes, specifically, G1 and S-phase arrest, were observed in absence of serum for four out of six SNPs tested. A size-dependent MN induction was observed: larger SNPs being more active in absence of serum. In addition, the serum influence was characterised by a size-dependency for cytotoxic and genotoxic effects, with a higher influence of serum for smaller particles. The data indicate that the in vitro micronucleus assay in presence and absence of serum could be advised for hazard assessment because it demonstrates a higher sensitivity in serum-free conditions than in conditions with serum. However, this recommendation applies only if the cell line used is able to proliferate under serum-free conditions because cell division is a prerequisite for MN expression.